Diverse temperate riparian buffer types promote system-level carbon sequestration in southern Ontario, Canada - Enoch Ofosu; Amir Bazrgar; Brent Coleman; Bill Deen; Andrew Gordon; Paul Voroney; Naresh Thevathasan (The Forestry Chronicle)
Riparian buffer systems (RBSs) can sequester atmospheric carbon dioxide into terrestrial carbon (C) pools. C stocks and C sequestration potential of diverse RBSs are not adequately reported. This study, therefore, quantified: (a) C stocks in various RBSs and (b) system-level C sequestration potentials (SLCSP) [SLCSP= ΔSOC + Biomass C Pools] in southern Ontario, Canada. Results showed significant differences (p < 0.05) in system-level C stocks between tree buffers (765.8 Mg C ha-1) and grass buffers (291.7 Mg C ha-1) and between natural forest buffers (935.9 Mg C ha-1) and rehabilitated buffers (595.6 Mg C ha-1), but no difference (p > 0.05) between coniferous buffers (722.4 Mg C ha-1) and deciduous buffers (809.1 Mg C ha-1) were recorded. Tree buffers had higher SLCSP (633.5 Mg C ha-1) than grass buffers (126.7 Mg C ha-1). Natural forest buffers had higher SLCSP (806.7 Mg C ha1) than rehabilitated buffers (460.3 Mg C ha-1). There was no difference (p > 0.05) in SLCSP between coniferous buffers (615.0 Mg C ha-1) and deciduous buffers (652.1 Mg C ha-1). Results from this study confirm that the establishment of RBSs within agricultural watersheds can significantly contribute to create new terrestrial C sinks.